2010
DOI: 10.1083/jcb1906oia14
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of lymphangiogenesis via VEGFR-3 inhibits chronic skin inflammation

Abstract: The role of lymphangiogenesis in inflammation has remained unclear. To investigate the role of lymphatic versus blood vasculature in chronic skin inflammation, we inhibited vascular endothelial growth factor (VEGF) receptor (VEGFR) signaling by function-blocking antibodies in the established keratin 14 (K14)-VEGF-A transgenic (Tg) mouse model of chronic cutaneous inflammation. Although treatment with an anti-VEGFR-2 antibody inhibited skin inflammation, epidermal hyperplasia, inflammatory infiltration, and ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 44 publications
4
48
0
4
Order By: Relevance
“…IL-37 overexpressing keratinocytes stimulated with M5 expressed lower levels of IL-6, IL-13, and psoriasin [15]. Keratin 14 VEGF-Atransgenic (K14-VEGF-tg) mouse model is a well-known psoriasis model, where VEGF is overexpressed in the epidermis, and the mouse spontaneously develops a chronic inflammatory skin disease with many features similar to human psoriasis [30]. K14-VEGF-tg mice injected with IL-37 displayed mild symptoms, such as scattered calluses, barely visible diabrosis, and scales, but histological analysis displayed psoriatic disease in mice treated with medium, characterized by epithelial parakeratosis and keratoplasia, severe lymphocyte infiltration into the dermis and epidermal layers, and apparent angiectasis.…”
Section: Il-37 In the Development Of Autoimmune Diseasesmentioning
confidence: 98%
“…IL-37 overexpressing keratinocytes stimulated with M5 expressed lower levels of IL-6, IL-13, and psoriasin [15]. Keratin 14 VEGF-Atransgenic (K14-VEGF-tg) mouse model is a well-known psoriasis model, where VEGF is overexpressed in the epidermis, and the mouse spontaneously develops a chronic inflammatory skin disease with many features similar to human psoriasis [30]. K14-VEGF-tg mice injected with IL-37 displayed mild symptoms, such as scattered calluses, barely visible diabrosis, and scales, but histological analysis displayed psoriatic disease in mice treated with medium, characterized by epithelial parakeratosis and keratoplasia, severe lymphocyte infiltration into the dermis and epidermal layers, and apparent angiectasis.…”
Section: Il-37 In the Development Of Autoimmune Diseasesmentioning
confidence: 98%
“…Other studies using two models of acute cutaneous inflammation (one of oxazolone-induced delayed-type hypersensitivity reactions and ultraviolet B irradiation) in VEGF-C and VEGF-D transgenic mice reported that the delivery of VEGF-C-and VEGFR-3-specific ligand significantly limited acute skin inflammation. They concluded that the increased network of lymphatic vessels in these mice significantly enhanced lymphatic drainage with no major change of the inflammatory cell infiltrate or the composition of the inflammatory cytokine milieu (Huggenberger et al 2010(Huggenberger et al , 2011Kajiya et al 2009). …”
Section: Lymphangiogenesis: Step By Step From Friendship To Hostilitymentioning
confidence: 99%
“…13 Lymphatic vessels dynamically participate in inflammatory reactions, modulate immune responses and immune tolerance, and respond to increased fluid loads in the tissue. They expand in inflammation, and their activation reduces the severity of tissue inflammation, 14 highlighting an emerging role of the lymphatic vasculature as a therapeutic target. Inflammation also constitutes a hallmark of lymphedema in the clinic as well as in experimental models, 5,15 and it has been reported that cyclooxygenase 2 inhibitors reduce the severity of experimental secondary lymphedema, indicating a potential involvement of inflammation in lymphedema development.…”
mentioning
confidence: 99%